Emotional arousal and its relationship to the level of job performance among female teachers Kindergarten (Journal of the College of Basic Education, 2023)
Summary of the research:The aim of the current research is to identify emotional arousal and the level of functional performance of kindergarten teachers and to define emotional arousal and functional performance of female teachers according to the length of service as well as to identify the correlation between emotional arousal and the level of functional performance of female teachers. (26) items, as well as the job performance measure consisting of (40) items distributed over three domains. The first and second domains may consist of (13) items for each domain, and the third domain is composed of (14), noting that the answer alternatives for the two scales are (1, 2, 3, 4,5) paragraphs, and the research sample consisted of (400) female teachers chosen by simple random method from (50) kindergartens from the Directorate of Education of Baghdad Governorate, Al-Rusafa, the first, second, and third, and using the statistical bag for social sciences (spss). The study concluded the following results: Good emotional arousal and job performance, and there are differences in emotional arousal according to the service variable in favor of the least service, and there are no differences in the level of job performance according to the service variable, in addition to the existence of a correlation between emotional arousal and the level of job performance.Keywords: emotional arousal, female teachers, job performance, kindergarten.